Tingkat Kemiskinan Pada Rumah Tangga Di Kota Banjarmasin - Adinda Fitria Febrianty; Khairi Pahlevi (PPJP ULM, 2020)
This research aims are, (1) to know poverty potrait based on household poorcharateristic in Banjarmasin city, (2) to know relation of poor status with occupation inBanjarmasin city, (3) to know dominant characteristics differentiator poor householdand unpoor households in Banjarmasin city.The responden research are 100 households lived in Banjarmasin city. Technicalanalysis used descriptive statistics and CHAID analysis.The result research show that characteristics of poor households are differentswith indicator percentage 22%, the relation between poverty status with occupationstatus households are strongest and generally the dominant indicator to different poorhouseholds with unpoor households are the households can not paying to medicinceservice on policlinic/hospital, not have saving or goods to sale with minimum valueRp500.000, occupation with salary under Rp600.000 and never/one times week toconsumtion milk.